(3eHOC OhGe Mb GdedcjI hGKQ eVi GdeOI ai GfbVGFg ai GdbGfhf GdeOfi GdeUQi hGdTQjYI GdGSdGejI (B/ s - (3YHOGdfGUQ acQi eMeOs; (3GfhQ eMehO OHhQ s; (3YHOGdQTjO eCehf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2000)
(3CMcGe GdOhGe (B: (3JYQjag , eTQhYjJg , SeGJg , WHjYJg , JbSjeGJg , GdOhGe GdehVhYj , GdOhGe GdbGfhfj , GdOhGe GdLGeY GdbjhO GdhGQOI Ydi eHOC GdOhGe aj Gdabgjf, GdhXjaI GdGLJeGYjI ddedcjI , fRY GdedcjI ddefaYI GdYGeI , GdGYJQGVGJ GdJj JhGLg GdOhGe , GdJNdi Yf GdCTjGA , GdedcjI GdeDbJI JWHjbGJgG , GfJbGd GdedcjI HGdejQGK hGdhUjI , GdbSe GdKGfj CKQ eVi GdeOI aj GfbVGA GdOhGe , GdJYQja HeVj GdeOI, GNJdGa GdfXGejf GdbGfhfj h Gdabgj HUOO SbhW GdNUheI hGfbVGFgG , fhYi GdJbGOe h fXGe YOe SeGY GdOYhi , Mce SbhW GdMb HGdJbGOe , gd GdMbhb GdeDbJI JSbW HGdJbGOe , HYV GdbhGYO GdGLQGFjI aj Gdabgjf , cjajI MSGH GdeOI hHOA SQjGfgG , SdWI GdbGVj , CKQ GdfRhd Yf GdJbGOe aj GfbVGA GdOhGe , WHjYI GdMjGRI , OYhi GdGSJMbGb , Mce GdGeJOGO GdbGfhfj ddYbO , YOe GdGSJZdGd GdRQGYj , Mce GdGeJOGO GdbGfhfj dYbO EjLGQ GdCeGcf (B- (3eOi JbGOe GdOjhf , JbGOe Mbhb GdGQK , CKQ GdJbGOe HGdfSHI Edi OYGhi Gdhba , GdMb GdCOHi ddeDda h CKQ GdJbGOe aj GfbVGFgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi (B2000s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B596-612s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3eHOC OhGe GdedcjIs; (3edcjI GdCYjGfs; (3GdOhGe GdbGfhfj ddedcjIs; (3GfbVGA OhGe GdedcjIs; (3GfJbGd GdedcjI s; (3GdedcjI GdeDbJIs; (3GdGeJOGO GdbGfhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs